2020
DOI: 10.3389/fmicb.2020.01378
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Alkylcitric Acids in Aspergillus niger Involves Both Co-localized and Unlinked Genes

Abstract: Filamentous fungi are an abundant source of bioactive secondary metabolites (SMs). In many cases, the biosynthetic processes of SMs are not well understood. This work focuses on a group of SMs, the alkylcitric acids, each of which contains a saturated alkyl "tail," and a citrate-derived "head." We initially identified their biosynthetic gene cluster and the transcriptional regulator (akcR) involved in the biosynthesis of alkylcitrates in the filamentous fungus Aspergillus niger by examining the functional anno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 61 publications
3
18
0
Order By: Relevance
“…Previously, we reported that 9-HHIA and 10-HHIA produced by A. niger S17-5 have cytotoxic and polymer building block properties (Aso et al 2020;Sano et al 2020). Related studies have predicted that 9-HHIA and 10-HHIA are synthesized by the condensation of octanoyl-CoA, which is derived from caprylic acid, with oxaloacetic acid (Guti errez et al 2002;Cao et al 2019;Palys et al 2020). However, there have been no studies regarding the effects of the addition of caprylic acid on 9-HHIA and 10-HHIA production.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Previously, we reported that 9-HHIA and 10-HHIA produced by A. niger S17-5 have cytotoxic and polymer building block properties (Aso et al 2020;Sano et al 2020). Related studies have predicted that 9-HHIA and 10-HHIA are synthesized by the condensation of octanoyl-CoA, which is derived from caprylic acid, with oxaloacetic acid (Guti errez et al 2002;Cao et al 2019;Palys et al 2020). However, there have been no studies regarding the effects of the addition of caprylic acid on 9-HHIA and 10-HHIA production.…”
Section: Discussionmentioning
confidence: 98%
“…2019; Palys et al . 2020). However, there have been no studies regarding the effects of the addition of caprylic acid on 9‐HHIA and 10‐HHIA production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations